Design and Build an Android Based Gateway Controller using the MQTT Protocol - R Moch Maghrifi Dwi Candra Maghrifi; Mochammad Taufik; Nugroho Suharto (Politeknik Negeri Malang, 2023)
The gate is the most important component of a building's security system. Although almost all homes have gates, they are still opened and closed in the traditional manner. As technology advances, a remote control may be used to automatically open and close the gate. In this study, the author attempts to develop a gate utilizing an internet-connected microcontroller and an android smartphone application to make it simpler for users to manage and monitor the motor's status and eliminate the need for a remote control. The automatic gate prototype includes a track length of 3 meters, a 12 V dc gearbox motor, and a control system. The gate load standard is 15.40 kg. The study's findings employ the Internet of Things (IoT) to regulate and observe gate opening and closing as well as gather data on gate status and maintenance. According to test results, an average torque value of 78.44 Nm at an average current value of 10.25 A was obtained utilizing a mass load variation between 1 and 15 kg. Qos performance between Node MCU and Android application shows the quality of data transfer during deceleration with an average value of 34.3 seconds. The average throughput value is 149.6719 bps.